Risk factors for tube exposure as a late complication of glaucoma drainage implant surgery - Chaku M (Dove Medical Press, 2016)
Meenakshi Chaku,1 Peter A Netland,2 Kyoko Ishida,3 Douglas J Rhee4 1Department of Ophthalmology, Loyola University Chicago, Maywood, IL, 2Department of Ophthalmology, University of Virginia School of Medicine, Charlottesville, VA, USA; 3Department of Ophthalmology, Toho University, Tokyo, Japan; 4Department of Ophthalmology and Visual Sciences, Case Western Reserve University, Cleveland, OH, USA Purpose: The purpose of this study was to evaluate the risk factors for tube exposure after glaucoma drainage implant surgery.Patients and methods: This was a retrospective case-controlled observational study of 64 eyes from 64 patients. Thirty-two eyes of 32 patients with tube erosion requiring surgical revision were compared with 32 matched control eyes of 32 patients. Univariate and multivariate risk factor analyses were performed.Results: Mean age was significantly younger in the tube exposure group compared with the control group (48.2±28.1 years versus 67.3±18.0 years, respectively; P=0.003). The proportion of diabetic patients (12.5%) in the tube exposure group was significantly less (P=0.041) compared with the control group (37.5%). Comparisons of the type and position of the drainage implant were not significantly different between the two groups. The average time to tube exposure was 17.2±18.0 months after implantation of the drainage device. In both univariate and multivariate analyses, younger age (P=0.005 and P=0.027) and inflammation prior to tube exposure (P≤0.001 and P=0.004) were significant risk factors. Diabetes was a significant risk factor only in the univariate analysis (P=0.027).Conclusion: Younger age and inflammation were significant risk factors for tube exposure after drainage implant surgery. Keywords: glaucoma drainage implant complications, Ahmed Glaucoma Valve, Baerveldt implant, tube erosion, pericardial patch graft